2017
DOI: 10.1007/s10620-017-4805-6
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Disease Is Associated with Increased Risk of Reflux Esophagitis

Abstract: In this large cohort of Korean men and women, participants with NAFLD exhibited increased incidence of reflux esophagitis independent of possible confounders, suggesting that NAFLD contributes to the development of reflux esophagitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…A cross-sectional study which involved a total of 2340 individuals in Korea suggested that NAFLD was linked to an increased prevalence of reflux oesophagitis with unadjusted OR of 1.95 (95% CI: 1.47-2.60). 13 Again, a cross-sectional study totalling 17 445 Korean adults who underwent a health check and endoscopy found a 1.44-fold increased risk of erosive oesophagitis in nonobese nonalcoholic fatty liver disease, suggesting an independent association between NAFLD and oesophagitis regardless of obesity. 11 Similarly, Catanzaro et al found that NAFLD was linked to an increased prevalence of GERD symptoms in a cross-sectional study totalling 206 subjects and adjusting for multiple potential confounding factors (adjusted OR = 3.49, 95% CI: 2.24-5.44).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A cross-sectional study which involved a total of 2340 individuals in Korea suggested that NAFLD was linked to an increased prevalence of reflux oesophagitis with unadjusted OR of 1.95 (95% CI: 1.47-2.60). 13 Again, a cross-sectional study totalling 17 445 Korean adults who underwent a health check and endoscopy found a 1.44-fold increased risk of erosive oesophagitis in nonobese nonalcoholic fatty liver disease, suggesting an independent association between NAFLD and oesophagitis regardless of obesity. 11 Similarly, Catanzaro et al found that NAFLD was linked to an increased prevalence of GERD symptoms in a cross-sectional study totalling 206 subjects and adjusting for multiple potential confounding factors (adjusted OR = 3.49, 95% CI: 2.24-5.44).…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, this positive association between NAFLD and GERD remained significant after adjustment for age, sex, BMI, diabetes, triglyceride and other metabolic risk factors. 13 Again, a cross-sectional study totalling 17 445 Korean adults who underwent a health check and endoscopy found a 1.44-fold increased risk of erosive oesophagitis in nonobese nonalcoholic fatty liver disease, suggesting an independent association between NAFLD and oesophagitis regardless of obesity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In South Korea, the Industrial Safety and Health Law requires annual or biennial health screening examinations of all employees, offered free of charge. Upper endoscopy is widely performed as a part of routine comprehensive health examination in Korea [16].…”
Section: Methodsmentioning
confidence: 99%